Modern format of electronic scientific editions of social-humanistic sphere in the Internet - Vlasiuk, A. I. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper considers the results of statistic research regarding the visits of the site "Electronic publications of the materials of the conference "Humanism and Education" held 3rd March - 3rdJune 2008.